Evaluation of healthcare professionals' fears and quality of life regarding COVID-19; comparison of the two physician groups (Annals of Medical Research, 2021)
Aim: The COVID-19 pandemic not only causes morbidity and mortality around the world, but also causes anxiety and fear among people. Healthcare workers are one of the groups most commonly affected during the epidemic process. It has been determined that the main transmission in COVID-19 is through droplets. This study aimed to measure the fear and anxiety about COVID-19 and evaluate the quality of life in two physicians' groups; ENT physicians with direct contact and psychiatrists without direct contact with the respiratory tract while examining patients.Materials and Methods: One hundred twenty-seven physicians accepted to fill in the online questionnaire were included in the study. The questionnaire form consisting of sociodemographic data form, the Fear of COVID-19 Scale, and SF-36 was applied online.Results: The presence of a psychiatric disturbance diagnosis and the rate of receiving psychiatric support in the past were higher in the psychiatrist group. All other demographic data were similar in both groups. When the Fear of COVID-19 Scale subscales and total score, SF-36 subscales were compared, no significant difference was found between the two groups.Conclusions: Our findings emphasize that both groups of physicians' fears about the pandemic and their quality of life are affected at similar rates. Longitudinal studies are needed to investigate other factors affecting healthcare professionals in public health emergencies such as pandemics.
Keywords: COVID-19; fear; life quality; pandemic; physicians